Developing collaborative performance system framework for fresh produce supply chain in West Java, Indonesia - Susanto, Edi (2024)
Considering the current context of business competition, it exists not only between individual companies but also between supply chain organizations. Supply chain organizations in business competition need a performance system that enables all simultaneous performance in a collaborative performance with all parties involved. Fresh produce is an important element of a healthy lifestyle for most individuals. Studies on collaborative performance systems (CPS) in fresh produce supply chains (FPSC) have attracted public attention due to their important role in food availability, safety, and security (SAS). Unfortunately, the use of performance management systems (PMS) as part of supply chain management systems is still lacking, and studies focused on CPS in FPSC systems are still limited. Therefore, this study aim at determining the prospective application of CPS in FPSC. This study attempts to identify whether the implementation of CPS is proven to be successful in improving the performance of SC actors and provides evidence of whether CPS can improve the overall performance of the supply chain, explores the factors that influence the implementation of CPS, and develops a proposed framework to improve the implementation of CPS in the FPSC. The aim of this study was achieved through a thorough literature review, consists of the following: CPS in the supply chain, factors affecting CPS, individual company performance (CIP), and supply chain performance (SPO). The research methodology used a mixed method with a structural equation model-partial least squares (SEM-PLS) to evaluate theoretical models and hypotheses based on a sample of 190 respondents from FPSC partners. This study further employed a qualitative approach with semi-structured interviews with 21 farmer group informants (abbreviated as Gapoktan: farmer collectives are agricultural institutions formed to facilitate agricultural activities from the capital sector to processing agricultural products) and non-Gapoktan farmers, collectors/distributors, owners of transportation modes, supermarkets, experts in the field, academics and related associations. The mixed method approach is valuable for future research on CPS implementation development; practical contribution by investigating CPS factors that influence the composition of CPS actors, the influence of CIP and SPO that contribute to improving CPS implementation; the benefits and reasons why CPS needs to be implemented by producing certain CPS metrics, considered for the sustainability of CPS implementation in FPSC. These findings will help managers/owners and implementing farmers to understand external barriers and support for FPSC actors. In conclusion, these results have contributed to the literature on the implementation of CPS and the implications of its management for actors; managers should review and improve their multitasking and time management skills in engagement, supervision, and support at the partner and employee levels; a proactive approach is recommended to acquire external knowledge and integrate it with existing internal knowledge. Practitioners (academics/researchers) should take a long-term and holistic view of the overall benefits of implementing CPS rather than focusing only on the short-term benefits and risks usually associated with initial costs and hidden costs, seeking to gain management, motivation, and communication skills. The government is the policy maker; carry out the socialization of sustainability programs to activate all partners involved and provide appropriate education or knowledge to increase FPSC actors' understanding of sustainable development by the SDG.